A Case of Lysosomal Acid Lipase Deficiency Confirmed by Response to Sebelipase Alfa Therapy. Issue 6 (December 2020) - Shen, Joseph J.; Davis, Jessica L.; Hong, Xinying; Laningham, Fred H.; Gelb, Michael H.; Kim, Grace E.
Abstract : ABSTRACT: Lysosomal acid lipase (LAL) deficiency, or cholesterol ester storage disease, is a disorder affecting the breakdown of cholesterol esters and triglycerides within lysosomes. Clinical findings include hepatomegaly, hepatic dysfunction, and dyslipidemia with a wide range of phenotypic variability and age of onset. The available clinical and molecular information of the patient presented herein was consistent with a diagnosis of LAL deficiency, but her LAL activity assay repeatedly showed normal or borderline low results. Her response to enzyme replacement therapy and demonstrable deficiency on a newer specific enzymatic assay ultimately confirmed her diagnosis of LAL deficiency.